POST-EDITING OF MACHINE TRANSLATION OF AN ENGLISH-INTO- ARABIC TEXT BY TRANSLATION STUDENTS - MOHAMMED, SHILAN SAFAR; AL-RUBAI’I, ALYA M.H. AHMED (Journal of Duhok University, 2023)
Post-editing is a necessary process for the amendment of machine translated texts to produce an acceptable output. This study aims to enhance the competency of translation students in post-editing a machine-translated text and the efficiency of the end product in conveying the desired message to the reader. To fulfill this aim, an experiment was carried out to examine the ability of twelve 4th year translation students in the Departments of Translation at AL-Mustansiriyyah and Mosul universities to post-edit an English journalistic text into Arabic via google translate. The study followed a mixed-method research design. Quantitative data were analyzed within the Dynamic Quality Framework adapted by the Translation Automation User Society. The students’ post-editing performance was evaluated in terms of how many error types were made, as well as the effect of errors on the quality of the text. The analysis showed that the most common error types were: 62.5% accuracy, 15.2%fluency, 8.3%terminology, and 45.8%verity of language. The end quality level among students was 62% major, 23.6% minor, and 13.8% kudos. It was also found that the translation students generally made the same errors, probably because of their language competency level and their lack of post-editing skills